2021
DOI: 10.1007/s00376-021-0326-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of Microwave Radiances from Metop-C and Fengyun-3 C/D Satellites for a Northern European Limited-area Data Assimilation System

Abstract: MetCoOp is a Nordic collaboration on operational Numerical Weather Prediction based on a common limited-area km-scale ensemble system. The initial states are produced using a 3-dimensional variational data assimilation scheme utilizing a large amount of observations from conventional in-situ measurements, weather radars, global navigation satellite system, advanced scatterometer data and satellite radiances from various satellite platforms. A version of the forecasting system which is aimed for future operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The radiance assimilation is commonplace in limited-area (regional) NWP systems too, albeit their relative importance in such applications tends to be less. The most common use case for radiance data is from sounders operating at microwave and infrared wavelengths (e.g., Kazumori, 2014;Lin et al, 2017;Lindskog, Dybbroe & Randriamampianina, 2021). By now, a mature status has been reached also in the area of using microwave imagers (e.g., Geer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The radiance assimilation is commonplace in limited-area (regional) NWP systems too, albeit their relative importance in such applications tends to be less. The most common use case for radiance data is from sounders operating at microwave and infrared wavelengths (e.g., Kazumori, 2014;Lin et al, 2017;Lindskog, Dybbroe & Randriamampianina, 2021). By now, a mature status has been reached also in the area of using microwave imagers (e.g., Geer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Despite all these challenges, satellite radiances and in particular microwave data have positive impact on analyses and forecasts in LAMs (e.g. Randriamampianina et al (2019); Lindskog et al (2021)). In general, the use of radiance measurements is more straightforward over open ocean in clear-sky conditions and the complexity of their assimilation grows with the increased sensitivity to the non-ocean surface and over areas affected by precipitation and clouds.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al [12] revealed that the assimilation of both NCEP PREPBUFR and radiance data could capture the structure of the storm and reduce tracking errors for different lead-time forecasts, which caused the improvement of the initial conditions for the storm. Lindskog et al [13] used a large number of observations from traditional observations, radars, scatterometer data, and satellite radiances to produce initial states using 3DVAR and found that the assimilation of microwave humidity sounder 2 (MWHS2) and the Advanced Microwave Sounding (AMSU-A) radiances was beneficial in reducing systematic observation errors and excluding gross errors. The impacts of the assimilation of FY-3D MWHS2 radiance data under clear skies for Tropical Storm Ampil were studied by Xu et al [14].…”
Section: Introductionmentioning
confidence: 99%